MITOS PAN BALANG TAMAK DI DESA NONGAN KECAMATAN RENDANGKABUPATEN KARANGASEM: SASTRA LISAN - Pebriyani, Ni Komang Ari; Duija, I Nengah; Subagia, I Nyoman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
The gap of Pan Balang Tamak character who was usually known by Balinese people in general happened in Nongan Village, Rendang Distric, Karangasem Regency. Beyond Pan Balang Tamak character precisely was respected by showing himself in the term of Balang Tamak temple in Nongan Village. The connection of Pan Balang Tamak myth with the folklore material in the village including the tradition which use janggi in the meeting, village rules, Pan Balang Tamak temple, Bale Pegat temple, Shrine in Subak Petian, and Karang Suung. There is a widening story then like Pan Balang Tamak myth according to the family of the landlord in Subak Petian area which connected with the family tree of Pasek Prateka and Pan Balang Tamak myth which connected with Rejang Buah dance and Baris Kumbang they arise as the result of the behavior of Pan Balang TamakÂ’s daughters.